La visite royale comme réponse au stress territorial : les conséquences des manifestations rurales dans le Haut Atlas central et oriental marocain - David Goeury (L'Espace Politique)
Since 2003, the media coverage of the protests of the people of central and eastern High Atlas feeds a conflict between opposition forces and the regime, on the efficiency of the management of territorial stress by the central government. Power is accused of sanctioning people ready to sedition, by refusing to do necessary public development policies. In response to these criticisms, it combines infrastructures building and recognition policies, embodied by royal visit. The royal visit recreates a connection between monarch and people. There is then a complex set of stakeholders leading to the construction of a national iconography of a remote area.